Report to the Members of the Legislative Assembly of the Cook Islands on Constitutional Development - Aikman, C C; Davidson, J W; Wright, J B (Victoria University of Wellington Law Review, 1999)
This report assists the Legislative Assembly of the Cook Islands in defining their views on the political and constitutional development of the Cook Islands. The aim was to put the representatives of the Cook Islands in a position to present definitive proposals for a constitutional change to the New Zealand Government. The report recommends the constitutional makeup of the Cook Islands, including the makeup of the executive, legislative, and judicial branches. The Report also discusses the Cook Islands' continued relationship with the New Zealand Government, as well as the establishment of a Constitution. Dr Davidson states in a separate comment that he disagrees with the other authors on the role of the traditional leaders of the Cook Islands (Ariki).